Phycoerythrin Production by a Marine Osdilatoria (Cyanophyta) - Wan-Loy, Chu,; Alw, Afnani; Siew Moi, Phang (Malaysian Journal of Science, 2002)
The production of the commercially important pigment phycoerythrin by the marine cyanobacterium Oscillatoria UMACC 216 was investigated. The cultures from different stages of growth (day 2, 4, 6, 8 and 10) were harvested for the determination of phyocerythrin. Cells from the exponential phase contained the highest amounts of phycoerythrin (66.7 mg g^-1 dry weight). The cultures changed from red to green then yellow colour after attaining stationary phase. A separate batch of cultures was grown at salinities ranging from 5, 10, 15, 20 to 25 (control) parts per thousand (ppt). Cells grown at 15 ppt contained the highest amounts of phycoerythrin (114.7 mg g^-1 dry weight). The phycoerythrin content of Oscillatoria UMACC 216 was much higher than that reported for other cyanobacteria. Further studies to optimise phycoerythrin production by this alga are worthwhile.